The future of FemTech ethics & privacy – a global perspective - Najd Alfawzan; Markus Christen (BMC Medical Ethics, 2023)
Abstract We discuss the concept of women’s empowerment in FemTech, considering cultural and legal differences, ethical concerns, and legal consequences. We claim that it is crucial to prioritize privacy, a fundamental right, especially in the case of changes in laws related to women’s health, such as Roe v. Wade in the US.